The nexus between stakeholders' materiality and sustainable development goals: evidence from higher education institutions - Aras, Guler; Kutlu Furtuna, Ozlem; Hacioglu Kazak, Evrim (EMERALD GROUP PUBLISHING LTD, 2022)
Purpose The purpose of this study is to shed light on the association between stakeholders' materiality and the sustainable development goals (SDGs), highlighting how higher education institutions (HEIs) can pursue sustainable development and provide a holistic perspective by mapping material issues. This paper provides a clear understanding of the universities' role, specifically a state university in a developing country in fostering sustainable development. Particularly, this study identifies where the service industry and Yildiz Technical University (YTU) can contribute to the SDGs. Design/methodology/approach This methodology contains three stages. In the first stage, the Sustainability Accounting Standards Board categories have been mapped to the SDGs, in the second stage mapping of the service sector and its industries has been carried out. Additionally, the methodology was based on an exploratory case study. Findings This paper provides empirical results on the significance of the service sector, education and YTU in contributing to the SDGs. Moreover, this paper provides a framework by mapping the material issues on how the education sector can make contributions to the SDGs. Practical implications Exhibiting how HEIs' implement integrated thinking and voluntarily implemented International Integrated Reporting Council guidelines can assist policymakers to make regulations based on the voluntary reporting framework. Social implications This paper contributes to increasing academics' awareness of sustainability practices. The research process and findings of this study can assist policymakers to make regulations based on the HEIs' voluntary reporting framework. Originality/value This study is the first to identify specifically where the service industry and specifically a state university in a developing country can contribute to the SDGs and one of a few in the emerging academic studies. Additionally, how integrated reporting can contribute to value creation by establishing and proactively achieving the SDGs.
Keywords: Stakeholder theory; Sustainable development goals; Higher education institutions; Legitimacy theory; Materiality analysis; UNIVERSITIES; FUTURE; IMPLEMENTATION; CHALLENGES; MANAGEMENT; LEADERS; AGENDA; STATE; Science & Technology - Other Topics; Education & Educational Research